Corneal Tattooing with India Ink in a Young Male - Manpreet Kaur; Shakeen Singh; Manpreet Singh (Delhi Journal of Ophthalmology)
A 25 -years old male patient underwent left eye squint surgery for exotropia followed by corneal tattooing by India ink to stain the unsightly long standing corneal opacity and obtained a cosmetically satisfying outcome.